Detection some active Compounds in the Leaves and Stems of Local Coriander Plant - Coriandrum sativum L. - Raghad Z. Sulaiman; Yaseen M. Ahmed (Tikrit Journal of Pure Science)
This research aimed at studying some of the chemical compounds of the leaves and stems of a local plant "Coriander". Inclusive  chemical Detection for the most important active chemical compounds that exist in this plant were carried out. The most chemically effective groups of compounds were identified using the (FTIR) spectrophotometer. It was found that the leaves of this plant contain Glycosides, Saponins, Resins, Flavonieds, Alkaloids, Phenoles and Coumarines. The (pH) of leaves was found to be equal to (5.48). It was also found that the stems of this plant contain Flavonieds, Terpenes, Steroids, Glycosides, Coumarines, Saponins, Resins and Volatile Oils. The (pH) of stems was found to be equal to (5.46). The presence of these compounds in locally planted Coriander  makes it one of the important medical herbs. The results of this research confirm the medical significance of this plant results from the existence of the active compounds. It is recommended to encourage planting Coriander in Iraq for medical purposes.